Islamic Education According to Ahmad Dahlan's Perspective: Contribution and Implementation in A Modern Social Context - Agus, Ratna Etikasari (MA'ALIM: Jurnal Pendidikan Islam, 2024)
The thoughts of KH. Ahmad Dahlan are a practical reaction to the bad conditions faced by Muslims in Indonesia. Muslims are left behind in the political, social, and economic fields. KH. Ahmad Dahlan stated that Islamic education seeks to develop Muslims into individuals who are virtuous, pious in their religious beliefs, have broad insight and awareness of modern scientific issues, and are ready to fight for the progress of their society. The purpose of this study is to analyze Islamic education according to Ahmad Dahlan's thoughts in the contribution and implementation of the modern social context. This study is part of a qualitative research project using a systematic review approach. Systematic review is a method that uses evidence based on previous evidence through review, structured evaluation, classification, and categorization. The results of the study show: 1) Ahmad Dahlan has a view on the importance of personality formation as an important target of educational goals; 2) Islamic education needs to be open, innovative, and progressive in relation to improving the curriculum by including religious and general education materials in an integrative manner; 3) changes and renewal are able to integrate aspects of religious values and general knowledge, faith, and technological progress; 4) through the process of awareness, the social contextual pattern learning approach.